Commodity Price Expectations and the Interest Rate - Sargent, Thomas J. (Quarterly Journal of Economics, 1969)
I. Introduction, 127. — II. A loanable funds model, 130. — III. Empirical results, 132. — IV. Macauley's criticism reconsidered, 138. — V. Conclusions, 139.